The influence of work environmental risk factors on fatigue in the construction industry: a review of literature - Heng, Pei Pei; Hanizah Mohd Yusoff,; Rozita Hod,; Mohd. Hasni Ja’afar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The construction workers are performing manual tasks in harsh conditions. Various environmental risk factors could have significant influence on work fatigue. This review article discussed the environmental causal factors which involved in work fatigue development in the occupational health perspective, with the aim in enhancing the body of knowledge specifically in the construction industry so that mitigation measures and interventions can be formulated and implemented for fatigue prevention and productivity enhancement. Data derived from a total of 11 relevant articles identified climatic heat, vibration and elevation change as the major risk factors that associated with work fatigue. The mechanism of the environmental factors’ influences on muscle, mental and visual fatigue were understood, pointedly the underlying physiological alteration. Additionally, appropriate preventive measures in accordance to the OSHA guides including work-break cycles, work management, cool-down arrangements with drinking water were discussed. The limitation of existing OSH requirements on work limits at heat exposure was recognized, including the lack of consideration on personal characteristics therefore might inaccurately estimate the personal heat tolerance time. The proper understanding of the environmental stressors and its impact on workers production and safety performance may help construction organisations and regulatory body to develop strategies for workers protection and fatigue-related accidents prevention.